Variables used in a warehouse reallocation decision and an evaluation of an ABC-analysis system - A multiple-case study at a 3PL company - Asker, Erik; Claesson, Fredrik (My University, 2017)
In today's increasingly competitive and globalized market, companies are forced to focus on their core competencies to stay competitive. Within the 3PL market the conditions are no different and 3PLs are forced to optimize their operations to stay competitive. One approach to stay competitive is to reallocate products within the warehouse to maximize productivity and minimize costs. Reallocation is an improvement strategy that could improve the productivity, defined as order lines picked per man-hour, by moving high-volume movers to more accessible locations and low-volume movers to less accessible locations. This to ensure that the picking process can be completed as efficiently as possible. This thesis is a multiple-case study of the customers of the 3PL Schenker Logistics AB (SLOG), located in Landvetter, Sweden. SLOG is working with reallocations on a daily basis but are currently unsure of what criteria to consider before a reallocation decision is made and what the resulting productivity effect could be. As a means to improve the reallocation decision, SLOG has acquired a decision support system called System X that classifies products by applying an ABC-analysis. The purpose of this study is to investigate what variables that should be considered in a reallocation decision and how they affect the productivity outcome as well as evaluating System X. Throughout the study, qualitative interviews with key employees and managers of each customer at SLOG were the main technique used for collecting empirical data. The empirical findings were later compared with literature within the field to conclude what variables should be used in a reallocation decision. The study shows that the reallocation decision is very complex, with many potential variables to consider. In total 20 variables were identified that directly or indirectly affects the reallocation decision and the related productivity outcome. The variables were divided in two categories; input variables and wildcards. The first category having a direct and measurable effect on the productivity whilst the second category has a non-quantifiable effect on the productivity outcome. In addition, an Excel model was developed that calculates the productivity outcome of a reallocation decision, based on the identified input variables. Reallocation tests were performed and it was concluded that in general, reallocations should not be made in a random storage setting unless the remaining inventory level is high and the average pick quantity is low. In contrast, within a dedicated storage setting, reallocations generally result in a productivity increase. Finally, it is not recommended that System X should be used in its current form, due to its many limitations.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics